Village Fund Management Transparency: A Lesson Learned - Yulius Galendra Tulis; Intiyas Utami; Aprina Nugrahesthy Sulistya Hapsari (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
Village Funds is a program held by the government to improve the villagers’ standard of living. Village Funds existed since 2015. With a big amount of money, transparency of the fund’s management is needed. Jati Village is one of the villages that stated themselves as a village that have management transparency of Village Funds. This research is a qualitative research that describes the “lesson learned” in the management of Village Funds. This research used primary data that was collected by in-depth interview. The interviewees in this research are village’s officials and citizens. The result of this research showed that Jati Village’s management of Village Funds is transparent enough that they can be an example for other village to learn about transparent management of Village Funds. The lessons that can be learned are their officials, who always provide information to anyone without any cover ups except for information that can only be shared with a certain official like the inspectorates and BPKP, and the and management of village funds in accordance with government instructions contained in village fund management laws.